1997
DOI: 10.1093/emboj/16.9.2408
|View full text |Cite
|
Sign up to set email alerts
|

Ansclgene product lacking the transactivation domain induces bony abnormalities and cooperates with LMO1 to generate T-cell malignancies in transgenic mice

Abstract: The product of the scl (also called tal‐1 or TCL5) gene is a basic domain, helix–loop–helix (bHLH) transcription factor required for the development of hematopoietic cells. Additionally, scl gene disruption and dysregulation, by either chromosomal translocations or a site‐specific interstitial deletion whereby 5′ regulatory elements of the sil gene become juxtaposed to the body of the scl gene, is associated with T‐cell acute lymphoblastic leukemia (ALL) and T‐cell lymphoblastic lymphoma. Here we show that an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
141
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 57 publications
12
141
0
Order By: Relevance
“…In addition, tail abnormalities and hair loss occurred concurrently in individual mice. Of note, similar phenotypes have also been observed in SCL/TAL1 transgenic mice, in which SCL/TAL1 cDNA was driven by a ubiquitous regulatory element (Aplan et al, 1997). Thus, the observed phenotypes were due to the ectopic expression of LYL1 rather than by disrupting other genes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, tail abnormalities and hair loss occurred concurrently in individual mice. Of note, similar phenotypes have also been observed in SCL/TAL1 transgenic mice, in which SCL/TAL1 cDNA was driven by a ubiquitous regulatory element (Aplan et al, 1997). Thus, the observed phenotypes were due to the ectopic expression of LYL1 rather than by disrupting other genes.…”
Section: Discussionsupporting
confidence: 67%
“…Histological structures of major organs including brain, heart, lung, kidney and liver showed no obvious abnormality in these mice (data not shown). Similar phenomena, including embryonic lethality and abnormality in tail and hair, have also been observed in SCL/TAL1 transgenic mice (Aplan et al, 1997). Taken together, these data indicated that, similar to SCL/TAL1, aberrant expression of LYL1 disturbed normal development of the tail and hair follicles and could be lethal when expressed at high levels.…”
Section: Lyl1 Transgenic Micesupporting
confidence: 71%
“…While this issue cannot be resolved until its target genes are identi®ed, the observation that p300 augmented transcription by Tal1 coding sequences corresponding to its two principal protein products, at least in the context of GAL4-Tal1 fusion proteins, may have relevance to their respective actions. Although both isoforms were found to cooperate with LMO1 or LMO2 in inducing T-cell leukemia in transgenic mice (Aplan et al, 1997;Larson et al, 1996), it was suggested that by virtue of lacking an activation domain, pp24 TAL1 did so as a transdominant negative inhibitor (Aplan et al, 1997). In contrast, our results predict that both TAL1 gene products could act in association with p300 as positive transcriptional regulators, and, indeed, pp24 TAL1 and pp47 TAL1 were similarly e ective at transactivating a reporter gene with LMO1 and LMO2 (Ono et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…LMO1 and LMO2 contain tandem copies of a protein interaction motif termed the LIM domain and have each been shown to cooperate with TAL1 in inducing thymic neoplasms in bitransgenic mice (Aplan et al, 1997;Larson et al, 1996). LMO2 has also been identi®ed in DNA-binding complexes in erythroid cells containing TAL1, the zinc ®nger transcription factor GATA-1, and the LIM domain-binding protein Ldb1/NL1 (Wadman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to emulate the consequences of these chromosomal translocations have been made using transgenic mice with enforced expression of Lmo1 (Aplan et al, 1997;Fisch et al, 1992;McGuire et al, 1992) or Lmo2 in thymic T cells (Fisch et al, 1992;Larson et al, 1994Larson et al, , 1995Larson et al, , 1996Neale et al, 1995). In these model systems, clonal T cell tumours arise with a long latency suggesting that the transgene is necessary but not su cient for overt tumour development.…”
mentioning
confidence: 99%